Climate change disrupts the seasonal coupling of plant and soil microbial nutrient cycling in an alpine ecosystem - Arthur A. D. Broadbent; Lindsay K. Newbold; William J. Pritchard; Antonios Michas; Tim Goodall; Irene Cordero; Andrew Giunta; Helen S. K. Snell; Violette V. L. H. Pepper; Helen K. Grant; David X. Soto; Ruediger Kaufmann; et al. (Global Change Biology, 2024)
The seasonal coupling of plant and soil microbial nutrient demands is crucial for efficient ecosystem nutrient cycling and plant production, especially in strongly seasonal alpine ecosystems. Yet, how these seasonal nutrient cycling processes are modified by climate change and what the consequences are for nutrient loss and retention in alpine ecosystems remain unclear. Here, we explored how two pervasive climate change factors, reduced snow cover and shrub expansion, interactively modify the seasonal coupling of plant and soil microbial nitrogen (N) cycling in alpine grasslands, which are warming at double the rate of the global average. We found that the combination of reduced snow cover and shrub expansion disrupted the seasonal coupling of plant and soil N‐cycling, with pronounced effects in spring (shortly after snow melt) and autumn (at the onset of plant senescence). In combination, both climate change factors decreased plant organic N‐uptake by 70% and 82%, soil microbial biomass N by 19% and 38% and increased soil denitrifier abundances by 253% and 136% in spring and autumn, respectively. Shrub expansion also individually modified the seasonality of soil microbial community composition and stoichiometry towards more N‐limited conditions and slower nutrient cycling in spring and autumn. In winter, snow removal markedly reduced the fungal:bacterial biomass ratio, soil N pools and shifted bacterial community composition. Taken together, our findings suggest that interactions between climate change factors can disrupt the temporal coupling of plant and soil microbial N‐cycling processes in alpine grasslands. This could diminish the capacity of these globally widespread alpine ecosystems to retain N and support plant productivity under future climate change.

Soil bacterial and fungal communities show within field heterogeneity that varies by land management and distance metric - Fiona M. Seaton; Rob I. Griffiths; Tim Goodall; Inma Lebron; Lisa R. Norton (Soil Biology and Biochemistry, 2023)

Long-Term Drought and Warming Alter Soil Bacterial and Fungal Communities in an Upland Heathland - Fiona M. Seaton; Sabine Reinsch; Tim Goodall; Nicola White; Davey L. Jones; Robert I. Griffiths; Simon Creer; Andy Smith; Bridget A. Emmett; David A. Robinson (Ecosystems, 2022)
The response of soil microbial communities to a changing climate will impact global biogeochemical cycles, potentially leading to positive and negative feedbacks. However, our understanding of how soil microbial communities respond to climate change and the implications of these changes for future soil function is limited. Here, we assess the response of soil bacterial and fungal communities to long-term experimental climate change in a heathland organo-mineral soil. We analysed microbial communities using Illumina sequencing of the 16S rRNA gene and ITS2 region at two depths, from plots undergoing 4 and 18 years of in situ summer drought or warming. We also assessed the colonisation of Calluna vulgaris roots by ericoid and dark septate endophytic (DSE) fungi using microscopy after 16 years of climate treatment. We found significant changes in both the bacterial and fungal communities in response to drought and warming, likely mediated by changes in soil pH and electrical conductivity. Changes in the microbial communities were more pronounced after a longer period of climate manipulation. Additionally, the subsoil communities of the long-term warmed plots became similar to the topsoil. Ericoid mycorrhizal colonisation decreased with depth while DSEs increased; however, these trends with depth were removed by warming. We largely ascribe the observed changes in microbial communities to shifts in plant cover and subsequent feedback on soil physicochemical properties, especially pH. Our results demonstrate the importance of considering changes in soil microbial responses to climate change across different soil depths and after extended periods of time.

Shrub expansion modulates belowground impacts of changing snow conditions in alpine grasslands - Arthur A. D. Broadbent; Michael Bahn; William J. Pritchard; Lindsay K. Newbold; Tim Goodall; Andrew Guinta; Helen S. K. Snell; Irene Cordero; Antonios Michas; Helen K. Grant; David X. Soto; Rüdiger Kaufmann; et al. (Ecology Letters, 2022)
Climate change is disproportionately impacting mountain ecosystems, leading to large reductions in winter snow cover, earlier spring snowmelt and widespread shrub expansion into alpine grasslands. Yet, the combined effects of shrub expansion and changing snow conditions on abiotic and biotic soil properties remains poorly understood. We used complementary field experiments to show that reduced snow cover and earlier snowmelt have effects on soil microbial communities and functioning that persist into summer. However, ericaceous shrub expansion modulates a number of these impacts and has stronger belowground effects than changing snow conditions. Ericaceous shrub expansion did not alter snow depth or snowmelt timing but did increase the abundance of ericoid mycorrhizal fungi and oligotrophic bacteria, which was linked to decreased soil respiration and nitrogen availability. Our findings suggest that changing winter snow conditions have cross‐seasonal impacts on soil properties, but shifts in vegetation can modulate belowground effects of future alpine climate change.

Inhibitory effects of climate change on the growth and extracellular enzyme activities of a widespread Antarctic soil fungus - Marta Misiak; William P. Goodall‐Copestake; Tim H. Sparks; M. Roger Worland; Lynne Boddy; Naresh Magan; Peter Convey; David W. Hopkins; Kevin K. Newsham (Global Change Biology, 2021)
Temperatures approaching or exceeding 20°C have been measured during summer in polar regions at the surfaces of barren fellfield soils under cloudless skies around solar noon. However, despite the upper temperature limit for the growth of cold‐adapted microbes—which are abundant in polar soils and have pivotal roles in nutrient cycling—typically being close to this temperature, previous studies have not addressed the consequences of climate change for the metabolism of these organisms in the natural environment. Here in a 5‐year field experiment on Alexander Island in the southern maritime Antarctic, we show that the abundance of Pseudogymnoascus roseus , the most widespread decomposer fungus in maritime Antarctic fellfield soils, is reduced by 1–2 orders of magnitude when irrigated and nutrient‐amended soils are warmed to >20°C during summer. Laboratory experiments under conditions mimicking those during midsummer in the natural environment indicated that the hyphal extension rates of P. roseus isolates and the activities of five extracellular enzymes are reduced by 54%–96% at high water availability after exposure to temperatures cycling daily from 2 to 21°C and 2 to 24°C, relative to temperatures cycling from 2 to 18°C. Given that the temperatures of surface soils at the study site already reach 19°C during midsummer, the observations reported here suggest that, at predicted rates of warming arising from moderate greenhouse gas emissions, inhibitory effects of climate change on the metabolism of P. roseus could manifest themselves within the next few decades. Furthermore, with peak temperatures at the surfaces of fellfield soils at other maritime Antarctic locations and in High Arctic and alpine regions already exceeding 20°C during summer, the observations suggest that climate warming has the potential to inhibit the growth of other cold‐adapted microbes, with negative effects on soils as the Earth's climate continues to warm.

Inbreeding and inbreeding depression of early life traits in a cooperative mammal - JOHANNA F. NIELSEN; SINEAD ENGLISH; WILL P. GOODALL‐COPESTAKE; JINLIANG WANG; CRAIG A. WALLING; ANDREW W. BATEMAN; TOM P. FLOWER; ROBERT L. SUTCLIFFE; JAMIE SAMSON; NATHAN K. THAVARAJAH; LOESKE E. B. KRUUK; TIM H. CLUTTON‐BROCK; et al. (Molecular Ecology, 2012)
Mating between relatives often results in negative fitness consequences or inbreeding depression. However, the expression of inbreeding in populations of wild cooperative mammals and the effects of environmental, maternal and social factors on inbreeding depression in these systems are currently not well understood. This study uses pedigree‐based inbreeding coefficients from a long‐term study of meerkats ( Suricata suricatta ) in South Africa to reveal that 44% of the population have detectably non‐zero ( F > 0) inbreeding coefficients. 15% of these inbred individuals were the result of moderate inbreeding ( F ≥ 0.125), although such inbreeding events almost solely occurred when mating individuals had no prior experience of each other. Inbreeding depression was evident for a range of traits: pup mass at emergence from the natal burrow, hind‐foot length, growth until independence and juvenile survival. However, we found no evidence of significant inbreeding depression for skull and forearm length or for pup survival. This research provides a rare investigation into inbreeding in a cooperative mammal, revealing high levels of inbreeding, considerable negative consequences and complex interactions with the social environment.